Anxiety and depression among children and young people involved in family justice court proceedings: longitudinal national data linkage study - Lucy Griffiths (BJPsych Open, 2022)
BackgroundLittle is known about mental health problems of children and young people (CYP) involved with public and private law family court proceedings, and how these CYP fare compared to those not involved in these significant disruptions to family life.AimsThis study examined records of depression/anxiety in CYP involved in public and private law proceedings using linked population-level data across Wales.MethodRetrospective e-cohort study. We calculated the incidence of primary-care-recorded depression/anxiety among CYP involved in these proceedings and in a comparison group, using Poisson regression. Depression/anxiety outcomes following proceedings were evaluated using pairwise Cox regression, with age- and gender-matched controls of CYP who had no involvement with the courts.ResultsCYP in the public group had twice the risk of depression (adjusted incidence rate ratio aIRR = 2.2; 95% CI 1.9–2.6) and 20% higher risk of anxiety (aIRR = 1.2; 95% CI 1.0–1.5) relative to the comparison group. The private group had 60% higher risk of depression (aIRR = 1.6; 95% CI 1.4–1.7) and 30% higher risk of anxiety (aIRR = 1.3; 95% CI 1.2–1.4). Following private law proceedings, CYP were more likely to have depression (hazard ratio HR = 1.9; 95% CI 1.7–2.1), and anxiety (HR = 1.4; 95% CI 1.2–1.6) than the control group. Following public proceedings, CYP were more likely to have depression (HR = 2.1; 95% CI 1.7–2.5). Incidence of anxiety or depression following court proceedings was around 4%.ConclusionsFindings highlight the vulnerability of CYP involved in family court proceedings and increased risk of depression and anxiety. Schools, health professionals, social and family support workers have a role to play in identifying needs and ensuring CYP receive appropriate support before, during and after proceedings.